Portrait of Critical Thinking Disposition among English Education Freshmen: Implication to Teaching Syllabus Design - Wijayanti, Murti Ayu; Rima, Rosmania (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2025)
The disposition of students to engage in critical thinking is an essential requirement for developing critical thinking skills and significantly impacts their competency in critical thinking. However, the practice of critical thinking is hardly included into educational institutions. Consequently, this study is conducted to determine the portrait of critical thinking disposition among English education freshmen at a state university in Banten, Indonesia. The findings of this study will serve as the foundation for developing teaching syllabus in all subjects in English department. This study utilized descriptive qualitative method to analyze the characteristics of critical thinking disposition among first-year English education students. The study sample comprised of first-semester students who were currently enrolled in the English Education Department comprising 110 first-year students. The California Critical Thinking Disposition Inventory (CCTDI) assessment, developed by Facione in 2011, was employed to gather data regarding students’ disposition towards critical thinking. The research findings indicate that, on the whole, English education freshmen possess a favorable disposition towards critical thinking, as 48.18% of the students fall into the positive category of essential thinking ability, followed by 44.52% exhibiting a strong CTD. Meanwhile, 7.3% of the student respondents show an ambivalent CTD. Further, while the top three CTD indicators among the freshmen are truth-seeking, open-mindedness, and analyticity, the bottom three indicators of their critical thinking disposition comprise inquisitiveness, maturity of judgement, and self-confidence. The results suggest that the students are familiar enough in solving problems or seeking truth from diverse points of views, but lack of desire and bravery for learning to process own reasoning and making decisions. Integrating the latest findings into the structure and implementation of the English education syllabus has the potential to enhance students' disposition towards critical thinking, thereby impacting their long-term ability to think critically.